Syntax Acquisition in Early Childhood Through Flash-Cards - Fadilah Utami; Dewangga, Stevanus; Aghnaita, Aghnaita; Hidayati, Sri (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – Syntax acquisition is a gradual language level and essential language ability that determine childhood academic ability. The syntax needs to be stimulated in various ways. One of them is using flash-card games. This research aims to describe syntax acquisition in childhood through flash-cards.Design/methods/approach – This research method is descriptive qualitative research with data collection techniques through observations and interviews. This research’s subject is a six-year-old child with the initials HN.Findings – HN’s syntactic acquisition through flash-card has developed according to his development and age. Language development in syntax that HN obtains includes aspects of understanding and expressing language. HN syntax acquisition is also influenced by two factors that are natural and environmental.Research implications/limitations – This research is a limited mini-research performed on 1 study subject for two months. As for the flash-cards used, there are only ten kinds of flash-cards.Practical implications – This research is expected to be helpful as a reference regarding the stimulation of early childhood syntactic abilities through flash-cards. Academics and practitioners can develop various activities other for increasing syntax ability or developing flash-cards games that are more interesting and fun to be used for learning in childhood.Originality/value – This study still has limitations in taking the data. Therefore, the researcher hopes to conduct research with no limitations for the next. Paper type: Research paper